New roots in America's sacred ground: religion, race, and ethnicity in Indian America - Joshi, Khyati Y. (Rutgers University Press, 2010)
In this compelling look at second-generation Indian Americans, Khyati Y. Joshi draws on case studies and interviews with forty-one second-generation Indian Americans, analyzing their experiences involving religion, race, and ethnicity from elementary school to adulthood. As she maps the crossroads they encounter as they navigate between their homes and the wider American milieu, Joshi shows how their identities have developed differently from their parents' and their non-Indian peers' and how religion often exerted a dramatic effect. The experiences of Joshi's research participants reveal how